The promotion and enhancement of Tomar’s heritage: the creation of a viewpoints route - Marques, Célio Gonçalo (2021)
Tomar is a Portuguese city located in the centre of Portugal. Its history is closely linked to the history of Portugal, having been the headquarters of the Military Orders of the Temple and of Christ. The city of Tomar is characterized by a great artistic, cultural and natural wealth, being the Templar Castle and the Convent of Christ its greatest ex-libris. Less known but of great historical value are the viewpoints of this Templar city that allow tourists to enjoy the magnificent and diverse landscapes. In order to promote this heritage, this study aims to create the Viewpoints Route of Tomar. This route involves the study and characterization of the viewpoints, the development of the route and an investment in its promotion and accessibility (access roads, signs, cleaning, etc.). It is intended the use of information and communication technologies to provide information to tourists, namely QR codes, audio guides, virtual reality, augmented reality, among others. It is also intended to use gamification strategies (i.e. geocaching) and the presentation of information in several languages to increase the attractiveness of this heritage. In economic terms, these viewpoints routes are ways of attracting tourists to the region and to create value, promoting the development of infrastructures and new business models. At the same time, there are some environment damages which demands some procedures to assure sustainability.